Studi in Silico Seskuiterpen Hidrokarbon dari Resin Daemonorops Draco sebagai Kandidat Agen Antikanker - Nerdy N; Nilsya F. Zebua; Adelia Puspita R.N; Titi K. Hulu; Yulia Azzahra; Azzahra T.M. Simatupang; Nikasia G. Sitohang; Chindy T. Manullang (Universitas Muhammadiyah Manado, 2026)
Daemonorops draco is a rattan plant that produces resin traditionally used as medicine and is known to contain various bioactive compounds. Previous GC–MS analysis identified 42 active compounds in the resin of Daemonorops draco, including a group of sesquiterpene hydrocarbons suspected to contribute to its biological activities. This study aimed to evaluate the potential of six sesquiterpene hydrocarbons, namely α-cubebene, α-copaene, α-amorphene, δ-cadinene, aromadendrene, and viridiflorene, as anticancer candidates using an in silico approach. PASS Online prediction indicated that all compounds exhibit antineoplastic and apoptosis agonist activities with relatively high probability of activity (Pa) values and low probability of inactivity (Pi) values, particularly α-copaene, α-amorphene, and α-cubebene. Toxicity evaluation using ProTox 3.0 classified all compounds into Toxicity Class V with high LD₅₀ values, indicating low acute toxicity. ADMET analysis using pkCSM demonstrated favorable pharmacokinetic and safety profiles without major toxicity indications. Overall, sesquiterpene hydrocarbons from Daemonorops draco show potential as anticancer agents based on computational predictions.